INOVASI PELAYANAN PUBLIK DI BALAI PELAYANAN PENEMPATAN DAN PERLINDUNGAN TENAGA KERJA INDONESIA (BP3TKI) SEMARANG - Kurniasari, Herwinda; Sulandari, Susi (Journal of Public Policy and Management Review, 2017)
This research is to identify and describe the implementation of public service innovation in BP3TKI Semarang and the positive and negative factor that influence the implementation of public service in BP3TKI Semarang. This research is a qualitative descriptive study by collecting data through interview, library research, documentation and observation. Informants in this research was BP3TKI Semarang’s staff and Indonesia’s labor that comes from Central Java Province. This research uses the atrributes of innovation theory to identify the implementation of public service innovation in BP3TKI Semarang and the factors that influence the implementation of that public service innovation. The results obtained that the implementation of public service in BP3TKI Semarang can be said quite good. It is known through the results of the implementation of public service in BP3TKI Semarang based on several indicators, pleasure/ satisfaction, important component, balance of the needs, is unsuitable from the innovative’s attribut in a proper way, and there are several problems leave unsolved. Moreover, there also two obstacle that could obstruct the proceeding of innovation from public service in BP3TKI Semarang, such as the lack of management and the lack of Human resources and facilities or infrastructures. According to the result of this research, it can be concluded that the Innovation of public service in BP3TKI went well generally although, some indicators of research have to be fix and some obstacle factors have to be solved. The researcher proposed some suggestion such as recruiting employees, determining the institutional values, improve the management of facilities and infrastructure, providing technologyat Ahmad Yani Airport in Semarang and Soemarmo Adi Airport in Surakarta, and increasing network capacity in BP3TKI Semarang.